Attitude towards engineering ethical issues: a comparative study between Malaysian and Indonesian engineering undergraduates - Balamuralithara Balakrishnan (Tanjong Malim, 2020)
Attitude towards engineering ethical issues: a comparative study between Malaysian and Indonesian engineering undergraduates by Balamuralithara Balakrishnan